Incidence and risk factors of neonatal thrombocytopenia: a preliminary study - Nila Kusumasari; Rinawati Rohsiswatmo; Djajadiman Gatot; Darlan Darwis (Paediatrica Indonesiana, 2010)
Background Thrombocytopenia is the most common hematological abnormality in the neonatal period. Hemorrhagic manifestations are found in 10% cases of thrombocytopenia. Neonatal thrombocytopenia commonly assumed due to sepsis, despite many risk factors that may caused thrombocytopenia.Objective To obtain incidence and risk factors of neonatal thrombocytopenia.Methods A cross sectional study was conducted in April 2009. Complete blood counts investigation was performed before age of 24 hours, medical conditions and risk factors of mothers and subjects were noted, as well as hemorrhagic manifestations. Subjects with thrombocytopenia were followed for 2 weeks. The risk factors consisted of hypertension in pregnancy, pre-eclampsia, eclampsia, intrauterine growth retardation, gestational diabetes mellitus, perinatal infection, asphyxia, sepsis, and necrotizing enterocolitis.Results Neonatal thrombocytopenia was found 17 (12.1%) of 140 subjects, consisted of 88.2% early onset and 11.8% late onset. Significant risk factor of mother was pre-eclampsia (PR 3.97, 95%CI 1.70 to 9.25), while significant risk factors of neonates were asphyxia (PR 5.66, 95%CI 2.49 to 12.86), sepsis (PR 5.33, 95%CI 2.33-12.19) and necrotizing enterocolitis (p=0.014; PR 9.2 95% CI 5.17 to14.84). We found 29.4% hemorrhagic cases of neonatal thrombocytopenia (i.e.,. skin, gastrointestinal, intracranial hemorrhage).Conclusions The incidence of neonatal thrombocytopenia was 12.2%. Significant risk factor of mother that caused thrombocytopenia was pre-eclampsia, while risk factors of neonates were asphyxia, sepsis and necrotizing enterocolitis.[Paediatr Indones. 2010;50:31-7].